2008
DOI: 10.4102/sajip.v34i2.721
|View full text |Cite
|
Sign up to set email alerts
|

Store Image: Toward a Conceptual Model Part 1

Abstract: The lack of a universal definition and conceptual model of store image guided the aims for this research, namely to 1) delineate the underlying structure of the store image construct; 2) formulate a definition of store image; and 3) develop a model of the underlying theoretical structure of store image. An in-depth literature review was done to specify the domain and to delineate the underlying structure of this construct. The knowledge gained was incorporated into the model of apparel store image that served … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 94 publications
0
14
0
1
Order By: Relevance
“…Dominant facade has a salient role for retailers as a well-defined, strong character: it can simplify the purchase decision making process and shorten the time spent with searches. Figure 1 Model of apparel store image [26] Store image can be influenced by several factors. Among others it includes the scope of goods and provided services, the physical environment, sales personnel, public and available promotions.…”
Section: Store Imagementioning
confidence: 99%
See 1 more Smart Citation
“…Dominant facade has a salient role for retailers as a well-defined, strong character: it can simplify the purchase decision making process and shorten the time spent with searches. Figure 1 Model of apparel store image [26] Store image can be influenced by several factors. Among others it includes the scope of goods and provided services, the physical environment, sales personnel, public and available promotions.…”
Section: Store Imagementioning
confidence: 99%
“…Among others it includes the scope of goods and provided services, the physical environment, sales personnel, public and available promotions. [27] According to du Preez et al (2008) consumer variable related to store image have a multiplicity. [26] They identified a wide array of store attributes and subdimensions as it can be seen in Figure 1.…”
Section: Store Imagementioning
confidence: 99%
“…Deste modo, a imagem de um shopping center, constituído por diversas lojas, pode ser definida como um complexo construto multidimensional baseado na percepção de atributos tangíveis e intangíveis associados a diferentes dimensões (HAEDRICH, 1993;PREEZ;VISSER;NOORDWIK, 2008). Por meio das abordagens de imagem na perspectiva mercadológica, entende-se que a imagem de um empreendimento, como é o caso de um shopping center, pode ser analisada tanto por seus atributos funcionais quanto por seus atributos psicológicos, intangíveis, mas que são observados ou sentidos pelos consumidores.…”
Section: Imagens Como Representações Mentais Sociais E Na Perspectivunclassified
“…Now the question arise that why to study store image, customer attitude, perceived customer value, customer satisfaction, behavioral response and intentions in a linking manner. As the answer, author argue that store image, customer overall store attitude, perceived customer value, customer satisfaction and subsequently store loyalty have gained great importance in the retail stores settings, which aim to survive in the market and store image is a key factor for influencing customer satisfaction (Bluemer and Ruyter, 1998; Koo, 2003) and also affects positively on customer patronage intentions (Chang and Tu, 2005), moreover the role of store image for attracting and retaining the customers becomes extremely important (Du Preez et al, 2008). Researchers have pointed out the need for a comprehensive scale to measure store image with customer attitude and perceived value, and their impact on customer satisfaction and loyalty because it was deficient in research (Du Preez et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…As the answer, author argue that store image, customer overall store attitude, perceived customer value, customer satisfaction and subsequently store loyalty have gained great importance in the retail stores settings, which aim to survive in the market and store image is a key factor for influencing customer satisfaction (Bluemer and Ruyter, 1998; Koo, 2003) and also affects positively on customer patronage intentions (Chang and Tu, 2005), moreover the role of store image for attracting and retaining the customers becomes extremely important (Du Preez et al, 2008). Researchers have pointed out the need for a comprehensive scale to measure store image with customer attitude and perceived value, and their impact on customer satisfaction and loyalty because it was deficient in research (Du Preez et al, 2008). After the reviewing of existing literature, it is found that most of the studies on retail sector are reported from developed countries and no studies were identified that evaluate the impact of store image attributes, customer attitude and perceived customer value on customer satisfaction, behavioral response and intentions collectively in Indian retail store settings.…”
Section: Introductionmentioning
confidence: 99%